Extending forage production using mixtures in a Mediterranean rainfed environment - Melis R.A.M.; Dettori D.; Nieddu D.; Stangoni A.; Sassu M.; Porqueddu C. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Forage mixtures based on perennial grasses and legumes have a considerable interest for farmers in Mediterranean rainfed livestock systems, in order to extend the grazing season and establish temporary grasslands. Currently, in South European rainfed farming systems based on annual forage crops, some gaps in forage availability are experienced during early autumn and late spring. With the aim to assess dry matter production and forage availability along seasons and years, forage mixtures based on lucerne and perennial grasses (tall fescue and cocksfoot) were tested for three years in an experimental field in Sassari (Italy). The erect type of lucerne, both in pure stands and in binary mixtures, showed the highest productions among treatments (up to 12 t of dry matter per year). It also had the best seasonal forage distribution, being able to grow during the summer in rainfed conditions and during winters characterised by mild temperatures.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)